Produção de bovinos de corte mantidos em pastagem consorciada e irrigada - Molinete, Marcos Luis (2018)
The objective of this work was to evaluate the effect of irrigation and grass and legume intercropping on pasture production and animal performance. The work was conducted at the Universidade Tecnológica Federal do Paraná - Câmpus Dois Vizinhos, in an area of 3.1 ha divided into twelve modules. The base pasture used was the African Star (Cynodon nlemfuensis Vanderyst), which has been implemented since 2014. In order to carry out the work during the winter period, this base pasture was demoted and sowed diploid ryegrass (Lolium multiflorum L.) cv. Fepagro São Gabriel with a viable sowing density of 55 kg ha-1 and then planted throughout the area by no-tillage system, black oats (Avena strigosa schreb) cv. BRS139 with seed density of 60 kg ha-1 using 17 cm line spacing and common vetch (Vicia sativa L.) cv. Amethyst with 30 kg ha-1.For the accomplishment of the work in the winter period, this base pasture was demoted and were seeded to haul diploid ryegrass (Lolium multiflorum L.) cv. Fepagro São Gabriel, with a viable sowing density of 55 kg ha-1 and then overlapping throughout the area, by no-tillage system, black oats (Avena strigosa schreb) cv. BRS 139 with seed density of 60 kg ha-1 using 17 cm line spacing and common vetch (Vicia sativa L.) cv. Amethyst with 30 kg ha-1. The experimental design was a randomized block design with four treatments with three replicates (modules). The treatments were in winter and spring: IRRIG = African Star + Oat + Holly + Irrigation; IRRIG = African Star + Irrigation, TEST = African Star + Oats + Azevem LEG = African Star + Oats + Azevém + Leguminosa. While in the summer, the treatments were: IRRIG = African Star + Irrigation; IRRIG + LEG = African Star + residual Vetch; TEST = African Star; LEG = African star + residual of the Vetch. Pasture management was performed using 24 castrated Angus steers, with age and initial mean weight of 8 ± 2 months and 162 ± 11.3 kg of live weight (VW), respectively. Irrigated forages were negatively affected for DM, DIVMS, and NDT during the summer and the legume yielded lower levels of MM. Legume along with irrigation provided higher CP contents during the winter. Legume along with irrigation provided higher CP contents during the winter. Irrigated treatments provided higher forage mass in both pre and post grazing during the summer and in winter the oat leaf mass and total production were higher. During spring the vetch provided less mass of dead material in pre grazing and in the winter better F / C ratio in post grazing. Animal performance presented good results, but did not differ (p <0.05) between treatments. For the animal behavior in the winter season, irrigation provided a longer grazing time, less leisure time and a lower rumination efficiency of DM, and the animals that were under the vetch treatments obtained a larger number of feeding stations.